Role of Multidetector Computed Tomography in Diagnosis of Acquired Gastrointestinal Fistulas - Gitanjali Arora; Padma V. Badhe (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Introduction Fistulas are abnormal communication between two epithelialized surfaces. Gastrointestinal fistulas are communication between the gut and another epithelialized surface. Fistulas are classified according to anatomic (internal or external), physiologic (output volume), and etiologic characteristics. In the case of clinical suspicion of a fistula, a multidisciplinary approach helps in diagnosing and management. Multidetector computed tomography (MDCT) has an advantage over other imaging modalities due to its ability to reconstruct high-resolution images in seconds, which limits motion or peristalsis artifacts, and is ideal for patients who are uncooperative or who are seriously ill. Aim Evaluation of MDCT as an initial tool in the diagnosis and characterization of gastrointestinal fistulas. Methods During this prospective observational study, MDCT was used to assess patients with clinical suspicion of gastrointestinal fistulas. When necessary, contrast agents were used to identify the enteric fistulous tract. The etiology and characterization of the fistulas were determined. Further, the gastrointestinal fistulas were confirmed via endoscopy, cystoscopy, or surgery. Results The most common type of gastrointestinal fistula is enterocutaneous fistula (ECF) (39%) and the most common cause of gastrointestinal fistulas is postoperative (47%). ECFs were classified according to their etiology, anatomy, and favorable characteristics (85% favorable) along with complexity (64% complex) to aid in the management process. In addition to pancreaticopleural fistulas (22%), biliary (11%), esophageal (8%), and pelvic fistulas (19%) were also observed. There were 19% of fistulas (esophageal and biliary) that were asymptomatic. Endoscopy confirmed such asymptomatic fistulas that were not convincingly detected on CT. Conclusion In this study, we concluded that with the appropriate clinical history, MDCT can accurately depict enteric fistulas. In addition to characterizing fistulas, MDCT is equally useful for detecting secondary complications like inflammation, obstruction, or abscesses.